Keratinolytic bacteria from the feathers of wild Dark-eyed Juncos (Junco hyemalis). Issue 2 (May 2022) - Tran, Minh D.; Dille, John W.; Camden, Weslin L.; Brunt, Diamond; Rogers, Christopher M.; Schneegurt, Mark A.
We collected >300 bacterial isolates from overwintering Dark-eyed Juncos ( Junco hyemalis ) to find that ∼40% appear to degrade the structural protein of feathers using extracellular keratinase enzymes. A guild of bacteria (∼18% of total counts) grew significantly better on basal salt medium (BSM) plates containing feather meal than on BSM agar-only plates (∼8% total counts). The genus-level profile of the 107 most active keratinolytic bacterial isolates shows that nearly half are Bacillus species. Keratinolytic Frigoribacterium, Microbacterium, Okibacterium, Pantoea, Sphingomonas, Staphylococcus, and Stenotrophomonas were found, among others. Active isolates were shown to degrade whole feathers, used feather meal as a sole carbon and energy source, and produced zones of clearing indicative of extracellular proteases on milk agar plates. Our novel in vitro keratinase assay uses ninhydrin to quantitate the release of amino acids from exogenously added keratin, with Bacillus licheniformis str. ATCC 14580 serving as a positive control. Keratinolytic isolates were grown in the presence of feather meal to induce keratinase release and this conditioned medium, called the enzyme extract, was clarified by centrifugation and filtration. The enzyme reaction was completed in 30 min and was positively correlated with the amount of extract added, until reaching color saturation. Bacillus pumilus str. F166 was the most active isolate and Bacillus cereus str. F65 was about half as active as the positive control. Bacillus cereus str. F27 performed well too. We also have demonstrated strong keratinolytic activity against raw wool α-keratin. Juncos are long-distance migrant birds that carry bacteria on their feathers, both beneficial and harmful to plants. The abundant keratinolytic bacteria on feathers are capable of structurally damaging the feathers, potentially reducing bird fitness and reproductive success. Keratinases have uses in tanning, silage, and remediation. Keratinases may be useful in the treatment of onychomycoses and actinic keratoses in medical and veterinary settings.